(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Microfinance helps the poorest and most marginalized members of society to acquire assets, diversify their income sources, and lessen their susceptibility to economic hardship. For the poor and low-income families and their micro businesses, microfinance encompasses a wide variety of financial services, including loans, deposits, payments, insurance, and other financial products. Microfinance Institutions’ long-term viability is under doubt. An all-out effort is needed to assist build the embryonic Microfinance Industry while addressing the trade-off between outreach and sustainability. Financial services in rural areas and long-term national financial development are used to examine this problem in detail. The study which discussed about Microfinance Concept And Definition, Definition Of Microfinance Institutions, Purpose Of Microfinance, Access To Capital, Entrepreneurship And Self-Sufficiency, Improved Standards Of Living, Trickle-Down Benefits, Microfinance In India, Microfinance Scenario In India, Procedural Aspects Of Microfinance, The Growth Of The Microfinance Sector In India, SHG-Bank Linkage Model, Stages Of Group Formation, Saving And Lending Mechanism Under SBLP, Microfinance Broadly Covers The Following Activities, Microfinance Institutions (MFI) Model, Effectiveness Of Microfinance, Microfinance And Women Empowerment.